APPLICATION OF FENTON’S REAGENT ON REMEDIATION OF POLYCYCLIC AROMATIC HYDROCARBONs (PAHs) IN SPIKED SOIL - Nursiah La Nafie (Indonesian Journal of Chemistry, 2007)
Problem associated with Polycyclic Aromatic Hydrocarbons (PAHs) contaminated site in environmental media have received increasing attention. To resolve such problems, innovative in situ methods are urgently required. This work investigated the feasibility of using Fenton's Reagent to remediate PAHs in spiked soil. PAHs were spiked into soil to simulate contaminated soil. Fenton's Reagent (H2O2 + Fe2+) and surfactant were very efficient in destruction of PAHs including naphthalene, anthracene, fluoranthene, pyrene, and benzo(a)pyrene from spiked soil. It was indicated by the fact that more than 96% of PAHs were degraded in the solution and the spiked soil.